Pengaruh Teknik Relaksasi Pernafasan dan Olah Tubuh terhadap Pengurangan Ketidaknyamanan Ibu Hamil Trimester III - Muliatul Jannah; Alfiah Rahmawati (Journal of Issues in Midwifery, 2023)
Pregnancy is the most challenging and the happiest phase in every woman’s life in which a mother goes through physical and psychological changes. These physical changes will lead to discomforts to pregnant women. These discomforts may occur in their third trimester of pregnancy, such as backache, leg cramps, pain in pubic bones, false contraction, insomnia, breathing soreness, and fatigue. If these continue for a long time, it will have an impact on the readiness for the labor. These discomforts can be reduced by doing exercises. Exercises that can be done during pregnancy are practicing breathing techniques and body exercises (Prenatal Yoga). This study aims to find out the effect of breathing relaxation techniques and body exercises on the discomfort decrease in the third trimester of pregnant women. This type of study is Quasi Experiment with Non Equivalent Control Group approach. The study was conducted by examining the pregnant women’s discomforts in the third trimester before (pre-test) and after (post- test) practicing breathing techniques and body exercises (Prenatal Yoga). The population in this study were all the third trimester pregnant women who practiced breathing techniques and body exercises at Kasih Ibu Hospital. The sampling technique used was quota sampling. This study was conducted at Kasih Ibu Mother and Child Hospital in Tegal and carried out from October to November 2020. The Wilcoxon test results obtained p value = 0.000, then p = 0.000> = 0.05, it can be concluded that there is a significant difference between the discomfort of third trimester pregnant women before breathing relaxation techniques and body exercises and after breathing relaxation techniques and exercise body (yoga).